1992 - the environmental dimension : task force report on the environment and internal market - Task Force Environment and the Internal Market; Commission of the European Communities (Economica, 1990)
Conclusions (s. 82, 122, 146, 167, 194, 210, 232-233, 245, 263-264). Summary (s. 267-288).
Keywords: Euroopan yhteisöt : EY; ilmansuojelu; jätehuolto; sisämarkkinat; talouskasvu; ympäristönsuojelu